PERAN AUDIT OPERASIONAL PADA UNIT KARYA PENDIDIKAN SEKOLAH DASAR KATOLIK “X” di SUMENEP - Senny Harindahyani (Jurnal Akuntansi Bisnis, 2017)
The quality of primary and secondary education in Indonesia is still relatively low, due to low service standards in primary and secondary education accompanied by unchecked corruption within the Department of Education’s bureaucracy. In an effort to improve the quality of schools, there is a need for program evaluation on a regular basis, one of which is operational auditing. The purpose of this research is to gain a extensive understanding of the application of the operational audit in evaluating internal control at Catholic Primary School "X" in Sumenep. Audits are carried out in several stages, which can be broadly grouped into three stages, namely: planning or preliminary survey, implementation, and reporting. This research resulted in findings that indicate the internal controls on learning activities and management activities at Catholic Primary     School "X" still has weaknesses. From the findings of the audit carried out a development stage is carried out that aims to provide recommendations on the reporting stage in order to assist the management division in repairing these issues. The implementation of this audit is expected to improve the quality of education services in the Catholic Primary School "X" -Sumenep, aiming to reform educational institutions by setting a foundation of transparency and accountability.   Keywords: Operational Audit, Internal Control, Primary and Secondary Education, School.